2015
DOI: 10.2174/1568026615666141209160556
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Redox Activity. Its Potential Clinical Applications in Neurodegenerative Disorders

Abstract: Neurodegeneration is the hallmark of many chronic progressive neurogical disorders characterized by specific clinical, morphological and biochemical features. Central nervous system is very sensitive to oxidative stress, which is considered as a key factor of neurodegenerative disorders. Therefore, many therapeutical strategies are focused on molecules with redox activity to re-establish the equilibrium between pro and antioxidants. Due to the fact that melatonin readily crosses the blood- brain-barrier, conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 72 publications
(98 reference statements)
1
60
0
2
Order By: Relevance
“…It has been suggested that melatonin supplementation is beneficial in neurodegenerative disorders, by protecting brain cells from oxidative stress (Miller et al, 2015). These results are promising in view that transplanted kidneys are prone to oxidative stress-mediated injury by pre-transplant and posttransplant conditions that cause reperfusion injury or imbalance between oxidants and antioxidants (Nafar et al, 2011).…”
Section: Clinical Relevancementioning
confidence: 99%
“…It has been suggested that melatonin supplementation is beneficial in neurodegenerative disorders, by protecting brain cells from oxidative stress (Miller et al, 2015). These results are promising in view that transplanted kidneys are prone to oxidative stress-mediated injury by pre-transplant and posttransplant conditions that cause reperfusion injury or imbalance between oxidants and antioxidants (Nafar et al, 2011).…”
Section: Clinical Relevancementioning
confidence: 99%
“…It also has anti-oxidative, anti-inflammatory, free radical scavenger, anti-aging, and neuroprotective effects, which have been connected with the redox status of cells and tissues, thus suggesting its potential clinical role in various neurodegenerative diseases [22-24, 43]. Recently, it has been proposed that melatonin promotes irradiation-induced inhibition of neurogenesis [29, 44] and proliferation, and differentiation of neural stem cells during hypoxia [45].…”
Section: Discussionmentioning
confidence: 99%
“…In a few earlier studies with infantile rats, some exogenous chemicals, such as decorin and memantine as potential neuroprotective agents, were tested for a reduction of cytopathological changes in the hippocampus due to kaolin-induced hydrocephalus [20, 21]. However, the possible roles of endogenous chemicals such as melatonin in patients with dilated ventricles and cognitive impairment have not been completely understood yet, although they could have antioxidant, free radical scavenger, and neuroprotective effects in many disorders of the body [22-24]. In this study, we investigated the effects of exogenous melatonin administration on the chronic hydrocephalus-induced hippocampal changes in infantile rats using histochemical and immunohistochemical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative process may also be inhibited by NOS (41). It was reported that melatonin (10 mg daily/ 30 days) caused a statistically significant increase in antioxidative enzymes such as SOD and GPx and a decrease in malondialdehyde (MDA) in erythrocytes of SPMS patients (42).…”
Section: Inflammatory Mediators and Antioxidantsmentioning
confidence: 99%